Evaluasi dan Pengembangan Sistem BUMDes Wisata Kemiren Berbasis Web Studi Kasus www.kemiren.com - Anak Agung Gde Satia Utama; Eka Elmi Hikmawati; Elsya Herwiyanti; Fatmah Fatmah (Ekuitas: Jurnal Pendidikan Ekonomi, 2019)
The purpose of this study is to evaluate and provide a system model for the development of Village-Owned Enterprises (BUMDes) in Banyuwangi with the Kemiren Tourism website as a case study. The current system is still not optimal, where the website functions only as a marketing system. This research uses a qualitative approach with case studies. Data obtained from interviews, observations, website observations and documentation. The analysis technique uses triangulation by doing data reduction first, then producing coding, and interpreting the results and finally taking conclusions. The results of the proposed system model can extend the benefits of the website not only as a marketing tool, but can be used as a means of customer relations, other tourist relations and evaluation results that can increase the revenue of BUMDes